Development of Flash Cards to Help Write Short Stories for 5th Grade Elementary Students - Putri, Salma Aprilia; Juneau, Janelle L. (Jurnal Educatio FKIP UNMA, 2024)
This study investigates the effectiveness of "ALICE" Flash Cards as a learning medium to assist 5th-grade students in writing short stories. Recognizing the importance of writing in fostering creativity and critical thinking, the research addresses the challenges faced by students at SDN Sidorejo Lor 03 Salatiga, such as difficulties in developing themes, plots, and organizing sentences. The study employs a Research and Development (RnD) approach, integrating Sugiyono's methodology with the ADDIE model, encompassing analysis, design, development, implementation, and evaluation phases. Initial needs analysis through teacher and student questionnaires identified a lack of engaging media for writing instruction. Consequently, "ALICE" Flash Cards were designed, incorporating theme, plot, and setting cards to guide story development. Expert validation rated the media as highly suitable, leading to revisions that included simplifying instructions and adding story examples. Field testing involved pre-tests, media treatments, and post-tests. Small group trials indicated high practicality with an 80/100 score, while the effectiveness was rated 78/100 based on students' writing performance. Evaluations from students and teachers confirmed the media's effectiveness, with scores of 75/100 and 84/100, respectively. Statistical analysis using the Wilcoxon Signed Ranks Test showed a significant improvement in students' writing abilities, with a p-value < 0.05, confirming the media's positive impact. In conclusion, "ALICE" Flash Cards proved to be a highly effective educational tool, significantly enhancing 5th-grade students' ability to write short stories. This research recommends their use as a practical and engaging aid in elementary writing instruction.